Data integration for multi‐path ultrasonic flowmeter based on Levenberg–Marquardt algorithm. Issue 8 (1st November 2015) - Tang, Xiaoyu; Xie, Xiang; Zhang, Hongjian; Zhou, Hongliang
Abstract : Ultrasonic flowmeters have potential for wide application in natural gas and hydrogen flow measurements in China. Accurate measurement is essential; thus, data fusion of acoustic paths is of importance. A data integration method for multi‐path flowmeter measurement is introduced and investigated in this study. The novel data integration method is based on the Levenberg–Marquardt algorithm. Computational fluid dynamics has been used to simulate the flows, and a laboratory scale system was established to obtain experimental measurements. The results of the simulations and experiments reveal that the method is able to reduce measurement error compared with four traditional integration methods in flow‐rate measuring in a long straight pipe. Furthermore, both the simulation and experiment results validate the integration method for non‐ideal flow conditions, such as flow downstream a single elbow or a 180° bend. The relative errors are within 1%, instead of more than 2%, which is typical for traditional methods.